Pengaruh Temperatur, Waktu Pemanasan, dan Komposisi Energizer BaCO3 terhadap Nilai Kekerasan dan Case Depth pada Proses Pack Carburizing Baja Karbon Rendah - Alfirano; Rike Kemala Putri; Anistasia Milandia (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2020)
Low carbon steel produced from the Hot Strip Mill process is widely used for hoe applications. In the application, this steel is expected to have a hardness value of 20 HRC to 41 HRC in accordance with SNI 0331:2011 to avoid failure when experiencing abrasion due to friction with sand and stone. Besides the hoe leaf also requires toughness on the steel core to receive shock loads during agricultural activities. To produce steel with these criteria, a carburizing pack process was carried out. This study was carried to increase the hardness of low carbon steel as a hoe application and determine the optimum temperature, heating time and composition of energizer for the pack carburizing process. In this study, the pack carburizing process was carried out with temperature variations of 850°C to 950°C, variations in heating time of 1-5 hours and variations in the composition of BaCO3 as an energizer of 20% and 80%. To determine the effect of temperature and heating time on hardness and microstructure, carburized steel was characterized for carbon content, hardness testing and metallography. The results of this study indicate that the higher the temperature and the heating time, the hardness of the steel will increase. Microstructure produced after the carburizing pack process is ferrite, pearlite and proeutectoid cementite. The carburizing pack process that produces the best hardness, case depth and microstructure values ​​is at a temperature of 950 ° C for 1 hour in BaCO3 composition of 20%.